2010
DOI: 10.1370/afm.1139
|View full text |Cite
|
Sign up to set email alerts
|

Validation of PHQ-2 and PHQ-9 to Screen for Major Depression in the Primary Care Population

Abstract: PURPOSE Although screening for unipolar depression is controversial, it is potentially an effi cient way to fi nd undetected cases and improve diagnostic acumen. Using a reference standard, we aimed to validate the 2-and 9-question Patient Health Questionnaires (PHQ-2 and PHQ-9) in primary care settings. The PHQ-2 comprises the fi rst 2 questions of the PHQ-9. METHODSConsecutive adult patients attending Auckland family practices completed the PHQ-9, after which they completed the Composite International Diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
768
1
25

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,052 publications
(840 citation statements)
references
References 16 publications
16
768
1
25
Order By: Relevance
“…In a previous study of the general primary care population, 11% of individuals were found to have a PHQ-2 score-3, 15 and the average POMS-B total mood disturbance score in a control population was reported to be 23.5. 23 For both of these assessments, the MPN population scores in the current study indicated a greater prevalence of mood symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study of the general primary care population, 11% of individuals were found to have a PHQ-2 score-3, 15 and the average POMS-B total mood disturbance score in a control population was reported to be 23.5. 23 For both of these assessments, the MPN population scores in the current study indicated a greater prevalence of mood symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…(34,35) Due to its brevity, the recommendation is to use the PHQ-2 simply as a screening tool for major depression and not for assessing disease severity. Among primary care doctors, (35) some recommend using a threshold score ≥ 2 (instead of ≥ 3) to improve sensitivity. Patients who obtain a score ≥ 2 should proceed to the nine-item Patient Health Questionnaire-9 (PHQ-9).…”
Section: How Do I Screen For Major Depression In Primary Care?mentioning
confidence: 99%
“…13 Our tobacco registry form included depression screening prompts, which also were included in the other chronic disease registries. 14 We have not reported on this variable because we could not examine individual contributions from this registry.…”
Section: Discussionmentioning
confidence: 99%